Pengaruh Kinerja Keuangan Terhadap Tingkat Kepercayaan Muzakki Untuk Membayar Zakat Profesi: Mampukah Kualitas Pelayanan Memoderasi? (Studi Kasus BAZNAS Kabupaten Sampang) - Firman Ardiansyah; Halida, Uly Mabruroh; Handayani, Sri; Bin Ahmad, Shofian (Shafin: Sharia Finance and Accounting Journal, 2025)
This study aims to examine and analyze financial performance which includes transparency of financial statements, financial accountability, and competence in managing funds on the level of muzakki's trust in paying professional zakat moderated by quality of service. This study uses a quantitative method with a causality approach. Data collection used questionnaires with accidental sampling techniques to ASNs in Sampang Regency. The data obtained is then processed through SPSS. Testing the variable starts from the multiple linear regression test, then the moderated multiple linear regression test. The results showed that the transparency of financial reports, financial accountability, and fund management competence had a significant effect on the level of muzakki's trust, as well as service quality had a significant effect but were unable to moderate the transparency of financial reports, financial accountability, and fund management competence on the level of muzakki's trust to pay professional zakat at BAZNAS Sampang Regency.